2014
DOI: 10.1016/j.immuni.2014.06.010
|View full text |Cite|
|
Sign up to set email alerts
|

Tumor-Associated Macrophages: From Mechanisms to Therapy

Abstract: The tumor microenvironment is a complex ecology of cells that evolves with and provides support to tumor cells during the transition to malignancy. Among the innate and adaptive immune cells recruited to the tumor site, macrophages are particularly abundant and are present at all stages of tumor progression. Clinical studies and experimental mouse models indicate these macrophages generally play a pro-tumoral role. In the primary tumor, macrophage can stimulate angiogenesis and enhance tumor cell invasion, mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

46
2,835
6
18

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 3,242 publications
(3,001 citation statements)
references
References 133 publications
46
2,835
6
18
Order By: Relevance
“…Newly recruited monocytes in the tumor are in contact with ATPderived nucleotides which may participate to the acquisition of an IL-10 high IL-12 low immunosuppressive phenotype. 10,60 As CD39 is located upstream the ATP metabolism, we hypothesized that manipulating the ATP/AMP ratio may modulate the immunosuppressive properties of M-CSF-macrophages. Accordingly, we observed that CD39 inhibition or adenosine depletion enhanced the capacity of activated TAM and M-CSF-macrophages to produce IL-1b and reduced their capacity to produce IL-10.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Newly recruited monocytes in the tumor are in contact with ATPderived nucleotides which may participate to the acquisition of an IL-10 high IL-12 low immunosuppressive phenotype. 10,60 As CD39 is located upstream the ATP metabolism, we hypothesized that manipulating the ATP/AMP ratio may modulate the immunosuppressive properties of M-CSF-macrophages. Accordingly, we observed that CD39 inhibition or adenosine depletion enhanced the capacity of activated TAM and M-CSF-macrophages to produce IL-1b and reduced their capacity to produce IL-10.…”
Section: Discussionmentioning
confidence: 99%
“…IL-10, VEGF, MMPs, IDO). 60 For this concern, to identify strategies that may inhibit their recruitment, block their generation, reverse their trophic and immunosuppressive roles or interfere with their survival may represent new therapeutic opportunities. 10 As a matter of fact, our study identifying the role of membrane CD39 in the acquisition and maintenance of an immunosuppressive phenotype by M-CSF-macrophages and TAM, could define ATP metabolism and IL-27 as privileged targets.…”
Section: Discussionmentioning
confidence: 99%
“…In colorectal carcinoma, TAMs have been shown to release growth factors, matrix-remodeling enzymes and promote vascularization. [7][8][9] The vascularization is often strictly dependent on macrophages and is fundamental for the tumor growth, invasion and metastatization. New vessels provide oxygen, nutrients and growth factors and allow cancer cells to extravasate and disseminate.…”
Section: Introductionmentioning
confidence: 99%
“…tumour‐associated macrophages)? Tumour‐associated macrophages are structurally plastic and heterogeneous, and functionally crucial for determining the fate of a tumour 52. These cells are widely accepted to be a cause of anti‐tumour immune suppression.…”
Section: Future Directionsmentioning
confidence: 99%